Peningkatan Profesionalisme Guru Dalam Proses Pembelajaran Melalui Supervisi KBM DI SDN Sambikerep II/480 Surabaya - Karomah Vidi Astutik (INNOVASI : JURNAL INOVASI PENDIDIKAN, 2025)
This study aimed to enhance the competence of teachers in developing teaching documents, particularly the Lesson Plans (RPP), through structured and continuous academic supervision at SDN Sambikerep II/480 Surabaya. The research was conducted using School Action Research (PTS) methodology in two cycles due to time constraints, which were deemed sufficient to observe improvements in teachers' ability to prepare teaching documents. The study involved classroom supervision to assess the alignment between the lesson plans and actual teaching practices, as well as an analysis of the originality of the syllabus and RPP developed by the teachers. The findings from the first cycle showed that only 44% of the teachers had completed their teaching documents adequately. However, after implementing a more interactive and media-supported supervision approach in the second cycle, there was a significant increase, with 95% of teachers successfully preparing comprehensive teaching documents. This increase indicates that targeted academic supervision, effective use of teaching media, and clear feedback can significantly enhance teachers' understanding and skills in creating effective and high-quality lesson plans. Further analysis confirmed that the syllabi and RPPs submitted by the teachers were genuinely their own work, as evidenced by the consistency between the planned and actual teaching scenarios observed in the classroom. The study also highlighted the importance of sustained guidance, practical examples, and feedback to motivate teachers to develop more complete and aligned lesson plans. This research contributes to the field of education by demonstrating the effectiveness of structured academic supervision in improving teaching quality at the primary school level. It recommends the continuation of ongoing training and guidance, the integration of diverse teaching media, and periodic evaluations to ensure that standards for RPP preparation are maintained and adapted to evolving curricula and student needs. This model of supervision could be adopted and further developed in other schools to foster professionalism and enhance the overall quality of education.